(untitled) (ҚазҰУ хабаршысы. Экономика сериясы, 2019)
Whilst social marketing has been continuing to capture increasing research attention in different settings across the globe, local movements and organizations in Kazakhstan are getting more involved in social marketing activities as well. The research objective of the current study is to explore the trends and challenges of social marketing in Kazakhstan. The study uses qualitative depth interview method. Combined mixed purposeful sampling approach was employed with maximum variation sampling technique used to select the participants. The phenomenological research was used to analyze qualitative data to generate meaning units and develop descriptions. The analysis of the sixteen interviews with experts revealed the major trends and challenges representing the current state of social marketing in Kazakhstan. The key findings of this study include the following: social marketing is growing and developing in Kazakhstan; the challenges facing social marketing in Kazakhstan include general misconceptions about marketing and social marketing, lack of funding and marketing expertise, and weak governmental support and regulation.